KAJIAN RANCANG BANGUN ALAT UKUR DEBIT AMBANG LEBAR DENGAN VARIASI KEMIRINGAN HILIR - Risman Risman; Warsiti Warsiti; Wasino Wasino; Mawardi Mawardi; Tedjo Mulyono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
The modeling of broad crested weirs is expected to facilitate understanding, especially the behavior of the flow flowing through the measuring instrument. The flow behavior under consideration is hydraulic behavior, measurement accuracy, and discharge curve. In addition, there is a relationship between discharge and water level upstream and downstream of the spillway, as well as the relationship of the variation of discharge flowing through the broad crested weirs to the loss of energy height. From the results of this study, it was found that there was a relationship between discharge and water level upstream, downstream, water level above the threshold, and energy loss for wide-threshold spillway. The modeling of the broad crested weirs assumes that the Froude number that occurs in the model is the same as the Froude number that occurs in the field. So that the scale of discharge, time, velocity and volume will be able to represent the actual conditions in the field. The scale of length, width, and height of the prototype is 1: 100. The methodology used is to carry out testing in the hydraulics laboratory by varying Q1, Q2, Q3, Q4, …. Qn, to obtain variations in water level upstream and downstream of the broad crested weirs. From the results of the study, it was found that the energy loss was relatively small with a trend of Y = 101.66x2 - 0.7359x + 0.0017 with the slope of the broad crested weirs downstream is 1:2, Y = 467.84x2 - 1.7816x + 0.0022 for slope of the broad crested weirs downstream is 1:1.5, and Y = -1140,4x2 + 0.6383x + 0.0077 with the slope of the broad crested weirs downstream is 1:1 where Y is the energy loss in meters and X is the discharge in m3/sec.